Naukratis: Trade in Archaic Greece - Möller, Astrid (Oxford University Press, 2000)
Archaic Naukratis was a busy trading place in the Western Delta of the Nile, renowned for its sanctuaries and courtesans, granting the Greeks access to Egyptian grain and luxury items. Now, more than one hundred years after the discovery and excavation of Naukratis, the author offers the first full-length analysis of the archaeology and archaic history of this important site. Although Naukratis always features in modern accounts of ancient Greek colonization, it was not a place where the Greeks could freely establish their own political and social organization–it was under the strict control of the Egyptian pharaoh and his officials. To understand the special status of Naukratis, the author takes the port of trade model, surveying the political, social, and economic background of both Late Period Egypt and archaic Greece. A major section of the book comprises an archaeological re-evaluation of the topography of archaic Naukratis and its material finds. The sanctuaries, archaic pottery styles, terracottas, faiences, statuettes, and other small finds are examined in the light of recent scholarship, and an in-depth study of the literary evidence is brought to bear on the archaeological material. This book comprises a significant contribution to our understanding of Graeco-Egyptian relations during the seventh and sixth centuries BC and also demonstrates that Polanyian economic theory can play an invaluable rï¿½le in the ongoing debate about the concepts best employed to analyse the ancient Greek economy.
History; Archaeology
Keywords: Ancient Egypt; business & economics; economic history; history